Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar IPA Kelas V Sekolah Dasar - Hayati, Hayati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
To find out whether or not the learning objectives have been achieved, it can be seen from student learning outcomes. Learning outcomes are influenced by several factors, one of which is the selection of the right learning model. The purpose of this study was to improve science learning outcomes for class V at SDN 19 Gunung Tuleh using Problem Based Learning (PBL). This research is a Classroom Action Research (CAR) using quantitative methods with a descriptive approach. The data collection technique used observation techniques in the form of observation sheets for teacher teaching activities and student learning activities, as well as student learning outcomes. The analysis technique used is the percentage technique, which is to compare the learning outcomes of cycle I and cycle II. The results showed a significant increase in student learning outcomes. In the first cycle the percentage of student learning completeness is only 40% by using the PBL model in the second cycle student learning completeness reaches 88%. Thus the PBL model can improve science learning outcomes for fifth-grade students at SDN 19 Gunung Tuleh for the 2020/2021 Academic Year.